2011
DOI: 10.4103/1463-1741.80156
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of environmental noise: Research in Serbia

Abstract: Research on the cardiovascular effects of noise in Serbia started in the year 2002, including experimental studies on humans and epidemiological studies on the adult and children population of Belgrade and Pancevo. Experimental exposure to noise [L eq = 89 dB (A)] had a hypodynamic effect, significantly lowering the cardiac index, cardiac work, and pump performance (P < 0.01). The vasoconstrictive effect of noise was shown through the significant elevation of after-load (P < 0.01). In a cross-sectional populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 0 publications
0
28
0
2
Order By: Relevance
“…[26] Lepore et al, [27] concluded that compared with quiet-school children, noisy-school children had significantly lower increases in BP when exposed to either acute noise or non-noise stressors, indicative of a generalized habituation effect. Studies in Serbia [28,29] among schoolchildren and pre-school children indicated a raised BP among children from noisy schools and quiet residences compared with children from both quiet environments. There is no consistent evidence that the effect of traffic noise on cardiovascular diseases increases with age.…”
Section: Cardiovascular Effectsmentioning
confidence: 94%
“…[26] Lepore et al, [27] concluded that compared with quiet-school children, noisy-school children had significantly lower increases in BP when exposed to either acute noise or non-noise stressors, indicative of a generalized habituation effect. Studies in Serbia [28,29] among schoolchildren and pre-school children indicated a raised BP among children from noisy schools and quiet residences compared with children from both quiet environments. There is no consistent evidence that the effect of traffic noise on cardiovascular diseases increases with age.…”
Section: Cardiovascular Effectsmentioning
confidence: 94%
“…[47] studies in serbia among schoolchildren and preschool children indicated a raised bp among children from noisy schools and quiet residences, compared to children from both quiet environments. [22,48] there is no consistent evidence that in older than younger people. [48] bodin et al Found strong evidence for an age effect in the noise bp association, with a could account for differences in prevalence in future studies.…”
Section: Introductionmentioning
confidence: 96%
“…[22,48] there is no consistent evidence that in older than younger people. [48] bodin et al Found strong evidence for an age effect in the noise bp association, with a could account for differences in prevalence in future studies. [23] There is a differential, but inconclusive effect regarding gender differences in cardiovascular effects of noise.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A noise level of 45 dB(A) causes spontaneous awakening, and awakening as a result of such derangement occurs during sleep, whereas the strength of 50 dB(A) or more prevents a person from having any rest. It can be concluded that the permanent effect of noise decreases human life expectancy by 8-10 years [27].…”
Section: Introductionmentioning
confidence: 99%